PERENCANAAN PARIWISATA BERKELANJUTAN: STUDI ARAH PEMBANGUNAN DAN TATA RUANG PADA DESTINASI WISATA LAKKANG, KOTA MAKASSAR - Rois Dinan; Jasman (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2026)
The Lakkang area, located in the heart of Makassar City and flanked by the Tallo River and Pampang River, possesses significant potential as an ecology- and culture-based tourism destination. However, urban development pressures, land conversion, and suboptimal spatial planning and development in Lakkang tourism have created challenges in maintaining the balance between environmental conservation and the utilization of space for tourism activities. This study aims to examine the development direction and spatial plan conformity in the Lakkang area based on sustainable spatial planning principles. A qualitative descriptive approach was employed, utilizing spatial analysis methods and literature review. Data were collected through a review of spatial planning documents, field observations, and interviews with stakeholders, in this case, the Head of Lakkang Urban Village. The findings indicate that tourism development in Lakkang has not been fully aligned with the spatial structure and pattern stipulated in the Makassar City Spatial Plan (RTRW). There is potential overlap between protected functions and planned tourism infrastructure development, which threatens the sustainability of local ecosystems, particularly mangrove forests and productive agricultural land. To optimize tourism development in this area, stronger integration is needed between spatial planning policies and conservation-based tourism destination planning. A participatory approach involving local communities, along with the protection of ecological and cultural values, is key to creating a sustainable development direction. This study recommends strengthening regulations, reviewing zoning plans, and fostering cross-sector collaboration to ensure that development in Lakkang is not only economically beneficial but also environmentally sustainable and socially equitable.